Deaths From Alcoholic and Diabetic Ketoacidosis at Autopsy—A Comparison Study - Milroy, Christopher M.; Lal, Anita; Parai, Jacqueline L. (Academic forensic pathology, 2023)
Diabetes mellitus and alcoholism are common disorders that may result in sudden death. Ketoacidosis may occur in both conditions. Diagnosis is based on history, and post-mortem findings including biochemistry and toxicology. This study compares deaths from alcoholic and diabetic ketoacidosis from two centres with large autopsy workloads. In the study period 9332 deaths were autopsies with 151 deaths diagnosed as ketoacidosis (1.6%) with 82 (0.9 %) being diabetic ketoacidosis (DKA) and 48 (0.5%) alcoholic ketoacidosis (AKA) deaths. There were more male deaths in each group. The median age for DKA deaths was 51 years (range 19-79). The median age for AKA deaths was 55 years (range was 34-78). The BMI range in DKA deaths was 12.5 to 40.4 kg/m2, with a median of 21.9. The comparative figures for AKA deaths was a range of 11.3 - 38.3 with a median of 20.2. Acetone concentrations were statistically higher in diabetic compared with alcoholic deaths, mean of 33.7 mg/100 mL in DKA cases versus mean of 16.9 mg/100 mL in AKA cases. Both DKA and AKA deaths are seen more commonly in males than female and are typically people with low BMIs in their 50s.